Manajemen Kompensasi Dalam Meningkatkan Kinerja Guru Pada MTs Nurul Huda Desa Kempas Jaya, Kecamatan Senyerang, Kabupaten Tanjung Jabung Barat - Thamrin Mansyur; Ahmad Ridwan; Muhammad Sanusi; Muhammad Ersadunas (Journal Innovation In Education, 2023)
The aims of this study were 1) to determine the human resource management compensation system in education at MTs Nurul Huda Kempas Jaya Village, 2) to determine the inhibiting and supporting factors for the human resource management compensation system in education at MTs Nurul Huda Kempas Jaya Village, 3) to determine the implementation of the human resource management compensation system in improving teacher performance at MTs Nurul Huda Kempas Jaya Village. This type of research is field research, namely research conducted directly with the object of research and data collection is carried out in the field. Researchers are trying to uncover Public Relations Strategies in Increasing New Students at Madrasah Tsanawiyah Nurul Huda Kempas Jaya Village for the 2020/2021 Academic Year. The results of this study are (1) the human resource management compensation system in education at MTs Nurul Huda Kempas Jaya Village is all income in the form of money, direct and indirect goods received by teachers as compensation for services provided to MTs Nurul Huda Kempas Jaya Village . This compensation takes the form of salary, benefits, incentives, and benefits. (2) Inhibiting factors: delays in giving salaries because many SPP payments are in arrears and there are bailouts, there is often overtime work outside working hours so that more funds are needed for payment, employees are often absent without prior coordination so working hours are not filled by officers this results in reduced compensation. Supporting factors: not a large number of educational and educational staff so it is easier to coordinate internally. (3) Implementation of a human resource management compensation system in improving teacher performance, namely at MTs Nurul Huda Kempas Jaya Village, the provision of compensation can be said to be effective in increasing the performance of teachers and employees. Teachers feel more responsible for carrying out their duties and performance appraisals that can improve employment status can have an impact on the welfare obtained and continue to motivate teachers in carrying out their duties. The better the performance appraisal of a teacher, the increase in status and compensation received can be considered.